1982
DOI: 10.1002/eji.1830120314
|View full text |Cite
|
Sign up to set email alerts
|

Induction and augmentation of mitogen‐induced immune interferon production in human peripheral blood lymphocytes by Nα‐desacetylthymosin αl

Abstract: Treatment of human peripheral blood lymphocytes with cloned N alpha-desacetylthymosin alpha 1 induced interferon production. The kinetics is similar to that of mitogen-induced interferon induction. N alpha-desacetylthymosin alpha 1, in combination with mitogen, augments the amount of interferon produced. This interferon is immune interferon (IFN-gamma) as determined by sensitivity to pH 2, lack of neutralization by antibodies to IFN-alpha or IFN-beta and absence of activity of MDBK cells. Although the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

1984
1984
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 20 publications
1
15
0
4
Order By: Relevance
“…In vivo, TF-5 and Td| increase lymphokine production (MIF and y-IFN) in low responder strains challenged with bacillus Calmette-Guerin (BCG) and Candida albicans [41,50]. Several other groups have shown that TF-5 and Td| induce and/or enhance production of y-IFN in vitro [56] in humans, and in vivo in mice [31], Shoham et al [53] have shown enhanced y-IFN production by human PBL and in mice after exposure to TP-1. It also has been reported that FTS [44.…”
Section: Role Of Lymphokines In Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, TF-5 and Td| increase lymphokine production (MIF and y-IFN) in low responder strains challenged with bacillus Calmette-Guerin (BCG) and Candida albicans [41,50]. Several other groups have shown that TF-5 and Td| induce and/or enhance production of y-IFN in vitro [56] in humans, and in vivo in mice [31], Shoham et al [53] have shown enhanced y-IFN production by human PBL and in mice after exposure to TP-1. It also has been reported that FTS [44.…”
Section: Role Of Lymphokines In Agingmentioning
confidence: 99%
“…It has been reported that Tct| can enhance a-and y-IFN production in murine and hu man systems [22,31,56]. Since y-IFN is an important regulatory lymphokine whose pro duction may be by a different T cell subset (Lyt-2+) than IL-2 and CSF (Lyt+).…”
Section: Csfmentioning
confidence: 99%
“…It has been reported that F5 and thymosin a1 increase production of migration inhibition factor (MIF) in the mouse and guinea pig (18,19) and production of a-and y-IFN in mice (20) and humans (21). Thymulin (FTS, facteur thymique serique), another thymic factor, has been shown to increase TCGF production by cells of nude mice (22).…”
mentioning
confidence: 99%
“…The role of lymphokines in host immune surveillance is now widely accepted, and thymic preparations and peptides have all been reported to influence the production of these immune mediators. Thymosin a 1 (T c~ 1) and TS induce or enhance the production of IFN-7 by human peripheral blood lymphocytes [32,34], and IFN-c~ and IFN-y in murine systems [12,25], thymulin (FTS) [26,27], thymic humoral factor (THF) [10], thymosin fraction 5 (TF-5) [38], and porcine thymic hormone (PT1) [38] have all been reported to influence in vitro IL-2 production. Thus, FTS raised the in vitro IL-2 synthesis by immature T cells in murin thymus and in spleens of athymic nude mice [26,27].…”
Section: Discussionmentioning
confidence: 99%